The Influence of Organizational Culture, Work Morale and Organizational Citizenship Behavior on the Performance of Employees at Waled Regional Hospital - Nazwa Aulia Putri; Lisa Harry Sulistiyowati (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
This study examined the effects of Organizational Culture, Work Morale, and Organizational Citizenship Behavior (OCB) on the performance of non-healthcare employees at Waled Regional General Hospital, Cirebon Regency. A quantitative survey design was employed involving 148 non-healthcare employees selected using a saturated sampling technique. Data were collected through structured questionnaires and analyzed using SPSS version 26, including validity, reliability, classical assumption, and simple linear regression analyses followed by partial t-tests. The findings revealed that Organizational Culture had a positive and significant effect on employee performance (B = 0.452; β = 0.506; t = 4.843; p < 0.001). In contrast, Work Morale (t = 0.348; p = 0.729) and Organizational Citizenship Behavior (t = 1.689; p = 0.093) showed positive but statistically insignificant effects on employee performance. These findings indicate that Organizational Culture is the most influential factor in improving the performance of non-healthcare employees, while Work Morale and OCB alone are insufficient to produce significant performance improvements. This study provides practical implications for hospital human resource management by emphasizing the importance of strengthening organizational culture to enhance employee performance and offers a reference for future studies in public healthcare organizations